PENGARUH PRODUK, HARGA DAN PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PADA KEDAI KOPI MAS JUNS DI SAMARINDA - Pasoloran, - Inka (EKONOMIA, 2019)
To be able to improve decision of purchasing, cafe of Mas Juns have to have a strategy in marketing of coffee, that is by improving the quality of product, price which reached relative and service, so that can improve decision of purchasing in cafe of Mas Juns.Pursuant to t test, there is positive influence and significant between product to decision of purchasing at cafe of Mas Juns in Samarinda. There is positive influence and significant between price to decision of purchasing at cafe of Mas Juns in Samarinda. There is negative influence and not signifikan between service to decision of purchasing at cafe of Mas Juns in Samarinda. And result F test, there is positive influence and significant between product variable ( X1), Price (X2) and Service ( X3) by together to decision of purchasing (Y) at cafe of Mas Juns in Samarinda From result of this research expected can be used as input to Cafe of Mas Juns upon which consideration in order to make-up of decision of purchasing by conducting the make-up from quality of service and product by research into desire of consumer and conduct more accurate research again.